The concept of difference in the Holy Qur’an is an objective study (Journal of the College of Basic Education, 2024)
In fact, there is a relationship between the religious and social meaning throughout history of the concept of nations or nation at the ancient and modern cultural and social levels. The two meanings are related and mutually supportive. What is meant by the nation is individuals with clear ties such as language, history, gender, or religion, and who live in a particular area of the land, even if they are not subject to a specific political system. The reason for choosing the topic is to explain the concepts of the word nation or nations in the Holy Qur’an and to explain the opinions of some commentators. The word nation has a spiritual connection that is not limited by time and place and has a permanent and eternal character even after the end of the world. Due to the importance of this word, the word “nation” is mentioned in the Holy Qur’an forty-seven times. Among some of the verses in which the word nation is mentioned and which the commentators cite on many occasions is (You are the best nation brought forth for mankind). What is meant in this verse are the companions of the Prophet, may God bless him and grant him peace, who departed with him from Mecca. (He found over him a group of people providing water) Stories 23 i.e. a group. Of the people, (Indeed, we found our fathers following a nation) Ornament 22 that is, following a religion. Therefore, explaining the different purposes in the word nation in the Holy Qur’an is of great importance, and through this clear research we tried to study the concept of nations and the nation from multiple aspects through the most famous commentators, while mentioning some verses related to the word.